ANALISIS PENERAPAN ACTIVITY BASED COSTING PADA TARIF JASA RAWAT INAP RUMAH SAKIT UMUM DAERAH (RSUD) DEPATI HAMZAH KOTAPANGKALPINANG (Studi Kasus Pada Rumah Umum Daerah (RSUD) Depati Hamzah Kota Pangkalpinang) - J, Riska; Astuti, Nelly; Tri Setyo Mulyani, Hendarti (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This research is titled “Analisis Penerapan Activity Based Costing Pada Tarif Jasa Rawat InapRumah Sakit Umum Daerah (RSUD) Depati Hamzah Kota Pangkalpinang”. This study aims to determine how the determination of inpatient service tariffs by using activity-based costing in Rumah Sakit Umum Daerah (RSUD) Depati Hamzah Kota Pangkalpinang and to know how big the difference of inpatient service tariff by using activity based costing method. The data used from the hospital only includes data of 2017and the rate of inpatient services that will be examined is the type of general care for the room rate, except for the main child, burns and raffle room / isolation. The results of this study indicate that rates of hospitalization services using activity based costing conducted through three stages. The first stage is documenting data on the list of tariffs for hospitalization and then the second stage, is calculating the cost of hospitalization in a way collection costs in the cost pool which has similar activities and then the third stage calculating the difference in rates of hospitalization services based on activity based costing system with the previous hospitalization rates which use traditional accounting methods. From inpatient services tariff calculation using the ABC method, it is Known That the large difference with previous rates are as follows; ABC method gives more expensive results in all rooms for VIP Pavilion Rp. 152,371.18 or 58.05%, Main Delima Rp. 21,891.47 or 10.89%, Main Akasia Rp. 34,823.62 or 17.33%, Class I Orchid IDR 5,240.43 or 4.37%, Class II IDR 21,028.92 or 23.37%, Jasmine Class II IDR 23,918.47 or 26.58%, Class III IDR 28,171.90 or 44.72%, Nusa Indah Class III Rp 42,194.10 or 66.97%, Asoka Class II Rp 26,914.21 or 29.90%, Class III Rp 33,364.33 or 52.96%, Class II Roses Rp 33,473.61 or 37.19%, Class III Rp. 53,462.24 or 84.86%, ICU without Class Rp. 100,968.81 or 20.19%. The difference between the rates of inpatient services using traditional methods and the Activity Based Costing method is to use traditional methods cheaper and the method of Activity Based Costing is more expensive, Due Rumah Sakit Umum Daerah (RSUD) Depati Hamzah Kota Pangkalpinang always on the subsistence of the government.